Empowering Community Resilience: Utilization of Yard Land as a Sustainable Food Source to Overcome Stunting in Gonggang Village, Poncol District, Magetan Regency - Sumasto, Hery; Astuti Setiyani; Fitri Rohkmalia; Wisnu, Nurwening Tyas; Suhermin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The COVID-19 pandemic has exacerbated food security and stunting problems in villages, especially in Gonggang Village. Therefore, strategic efforts are needed to increase food security through the use of yard land as an alternative food source. The purpose of this service activity is to empower the village community in optimizing yard land to prevent stunting and increase food security. This service activity was carried out with a participatory approach for seven months, through training, coaching, and field practicum. This activity involved students from the Department of Midwifery and Environmental Health to support the community in managing yard land. The results of the activity showed that as many as 50% of the target partners succeeded in using their yards so that they became a source of food, and 100% of Posyandu cadres showed increased competence in early detection of the growth and development of toddlers. In addition, there was an increase in community participation in Posyandu with an achievement of more than 90%. Active community involvement in the program is essential, with support from governments, non-governmental agencies, and local communities, contributing to the program's success. The outputs of this program include activity videos, journal publications, and IPR (copyright), which is expected to be a reference for similar programs in the future. The conclusion of this activity is that the use of yard land as an alternative food source has proven to be effective in increasing food security and preventing stunting in Gonggang Village. This program shows the importance of collaboration between various parties to achieve common goals in community empowerment.